Hedging geopolitical risk with precious metals - Baur, Dirk G.; Smales, Lee A. (Journal of Banking & Finance, 2020)
We analyse the relationship between geopolitical risk and asset prices and show that geopolitical risk is distinct from existing measures of economic, financial, and political risk and that the response of precious metals to geopolitical risk differs considerably from that of other assets. Precious metals are hedges against geopolitical risk in general and geopolitical threats (as opposed to acts) in particular. Conversely, stocks and bonds respond negatively to geopolitical risk and geopolitical threats. For extreme geopolitical risks, only gold and silver display consistent safe haven properties. Our results show that holding precious metals within a diversified portfolio lowers the impact of geopolitical risk.